The SIMBOL ISLAMOFOBIA DALAM FILM PADMAAVAT DAN MY NAME IS KHAN BERDASARKAN KAJIAN SEMIOTIKA ROLAND BARTHES - Dadan Rusmana; Destya Nursifa Meylani (Ruang Kata, 2021)
This research aims to identify the symbols and meanings contained in the film Padmaavat and My Name Is Khan. The research problem consists of the many negative responses from the public to the film of Padmaavat because this film shows a cruel Muslim leader and is considered to be misleading many people, in addition the film of My Name is Khan is also related with the issue of terrorists after the WTC (World Trade Centre) incident in New York. To analyze these problems, the theory used is the semiotic analysis of Roland Barthes. This theory explained about denotation, connotation and myth. While the research method used is a qualitative approach that analysing the symbols of the film. This research resulted in the following conclusions. First, the meaning of denotation and connotation explained Roland Barthes' semiotic theory in each scene. Second, the meaning of myth explained the meaning believed and depicts Islamophobia in each scene. Key words: Film, Padmaavat, Islamophobia, analysis, symbols.